Distribution of fungi of the genus Septoria in the Northern Tien Shan (Ile Alatau and Kungey Alatau, Kazakhstan) - Assylbek, A. M.; Rakhimova , Y. V.; Yermekova , B. D.; Kyzmetova , L. A.; Jetigenova , U. K.; Sypabekkyzy, G. (Проблемы ботаники Южной Сибири и Монголии, 2021)
Data on the distribution of microscopic fungi of the genus Septoria in the Northern Tien Shan withinKazakhstan (Ile Alatau and Kungey Alatau) are presented. A list of the species of Septoria is given, indicating the familyand species of the affected plants. 78 species of fungi of the genus Septoria, developing on 90 plant species which belongto the 35th family were identified. According to our research, herbaceous plants are most susceptible to Septoria (86.6 %of the total number of species).